Hubungan Penerapan Feeding Rules Terhadap Perilaku Makan Pada Anak Usia Toddler - Sri Ardayani; Ganis Indriati; Juniar Ernawaty (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2026)
Introduction: The toddler period is a golden stage, particularly for the formation of children’s eating habits. The implementation of feeding rules, including schedule, environment, and feeding procedures, plays an important role in shaping healthy eating behavior. Objectives: This study aimed to determine the relationship between the implementation of feeding rules and eating behavior in toddlers. Methods: This research was a descriptive correlational study with a cross -sectional approach. The sample consi sted of 74 mothers who had toddlers in Payung Sekaki, selected using a total sampling technique. The instruments used were the Feeding Practices and Structure Questionnaire (FPSQ) and the Children’s Eating Behavior Questionnaire (CEBQ), both of which had been tested for validity and reliability. Data analysis was conducted using the Chi-Square test. Results: The study showed that among 38 respondents who implemented feeding rules correctly, 28 children (73.7%) were categorized as food enjoyers, while among 36 respondents who did not implement them correctly, 25 children (69.4%) were categorized as food avoiders. The study found a significant relationship between the implementation of feeding rules and eating behavior in toddlers (p = 0.000; α = 0.05). Conclusions: The more accurately parents apply feeding rules, the greater the likelihood that toddlers will develop positive eating behavior.